Biomarkers of tolerance in immune-mediated inflammatory diseases: a new era in clinical management?. (May 2021) - Baker, Kenneth F; Sim, Jasmine P X; Isaacs, John D
Summary: Modern therapeutic agents and treatment regimens have made sustained remission an attainable target for many patients across a spectrum of immune-mediated inflammatory diseases, albeit at the risk of adverse events and the expense of drug prescription and safety monitoring. Clinicians and patients are thus increasingly faced with a novel treatment dilemma: whether and how best to stop immunomodulatory treatment in patients who achieve remission. In this final paper in a Series on therapeutic tolerance induction, we summarise our current knowledge of biomarkers of immune homeostasis in immune-mediated inflammatory diseases and their application to the prediction and attainment of sustained drug-free remission. We summarise evidence from prospective studies of immunomodulatory drug cessation across a range of immune-mediated inflammatory diseases, including rheumatoid arthritis, juvenile idiopathic arthritis, and inflammatory bowel disease. We also consider current evidence for clinical, serological, proteomic, metabolomic, cellular, and microbiomic biomarkers of immune homeostasis. Finally, we discuss the steps necessary for clinical translation of these biomarkers, as well as the potential transformative effect of these biomarkers on management of patients with immune-mediated inflammatory diseases if clinical translation is successfully achieved.